1999
DOI: 10.1088/0953-4075/32/11/305
|View full text |Cite
|
Sign up to set email alerts
|

Observation of post-collision interaction (PCI) in HBr using two-dimensional photoelectron spectroscopy

Abstract: The creation and subsequent Auger decay of the 3d −1 core-hole state in HBr is studied using two-dimensional photoelectron spectroscopy. In this technique the yield of electrons is collected as a function of both photon and electron kinetic energy. The effects of post-collision interaction (PCI) observed in the energy shift of the HBr + (3d −1 ) photoelectron lines. The energy shifts are compared with previous experimental results on Kr. This comparison suggests that the molecular nature of HBr has little effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Note the decreasing influence of the PCI tail on the peaks for higher photon energies due to the higher kinetic energy of the photoelectron. This is in good agreement with a recent experimental study of the PCI effect in HBr [24]. In addition to the intense transitions from the vibrational ground state in the electronic ground state (v = 0) to the vibrational ground state in the ionized state (v = 0), weak transitions to the first vibrationally excited state in the ionized state (v = 0 → v = 1) can be seen, reflecting a small change in the equilibrium distance upon ionization.…”
Section: Resultssupporting
confidence: 93%
“…Note the decreasing influence of the PCI tail on the peaks for higher photon energies due to the higher kinetic energy of the photoelectron. This is in good agreement with a recent experimental study of the PCI effect in HBr [24]. In addition to the intense transitions from the vibrational ground state in the electronic ground state (v = 0) to the vibrational ground state in the ionized state (v = 0), weak transitions to the first vibrationally excited state in the ionized state (v = 0 → v = 1) can be seen, reflecting a small change in the equilibrium distance upon ionization.…”
Section: Resultssupporting
confidence: 93%
“…The influence of the PCI effect on the Br 3d −1 photoelectron lines of HBr has been studied to date by Odling-Smee et al [51]. In their study the photon energy was varied while the influence of the kinetic energy of the individual Auger electron was not taken into account.…”
Section: A Deceleration Of the 3d −1 Photoelectron Caused By The Pcimentioning
confidence: 99%
“…Therefore, with the assumption of sufficient experimental energy resolution all the above factors assume the possibility of measuring the energy shifts for the 2 S and 3 + u lines. Concerning the latter, note that the previous studies of the PCI effect in the molecules N 2 O [11] and HBr [12] showed that the theory developed for atomic targets [5,13] gives a satisfactory description of the data on the PCI.…”
Section: Introductionmentioning
confidence: 99%